Occupational skin cancer - Diepgen, Thomas L.; Drexler, Hans (Kanerva's Occupational Dermatology, 2019)
Occupational skin cancer can be induced due to industrial exposure to chemical carcinogens but nowadays more important due to occupational exposure to UV radiation (UVR). Occupational skin cancer is characterized by long induction periods (years or decades), and its first manifestation is often seen many years after the occupational exposure or even when the affected individuals are not more occupationally exposed. Important industrial chemicals are arsenic and inorganic arsenic compounds, polycyclic aromatic hydrocarbons (PAHs) with particularly high levels in brown coal tars (soft coal tars), coal tars (black coal tars), coal tar pitches, coal tar oils, and coke oven emissions and can cause basal cell carcinomas and squamous cell carcinomas. A published systematic appraisal of the epidemiologic literature and meta-analysis clearly indicates that occupational UV-light exposure is a substantial and robust risk factor for the development of cutaneous squamous cell carcinoma (SCC). The actually available evidence of the epidemiologic literature could also clearly show a significant risk increase for occupationally UV-exposed workers to develop basal cell carcinoma (BCC) compared to nonexposed workers. There is enough scientific evidence that outdoor workers have an increased risk to develop work-related occupational skin cancer due to natural UVR exposure, and adequate prevention strategies have to be implemented. The three measures that are successful and of particular importance in the prevention of nonmelanoma skin cancer in outdoor workers are the following: 1. Changes in behavior regarding awareness of health and disease resulting from exposure to natural UV radiation 2. Protection from direct UV radiation by wearing suitable clothing 3. Regular and correct use of appropriate sunscreens.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Actinic (solar) keratoses; Bowen’s disease; Keratoacanthoma; Malignant melanoma; Nonmelanoma skin cancer; Pitch skin disease; Tar keratoses